2014
DOI: 10.1017/s0007114513004261
|View full text |Cite
|
Sign up to set email alerts
|

Xylo-oligosaccharides alone or in synbiotic combination withBifidobacterium animalissubsp.lactisinduce bifidogenesis and modulate markers of immune function in healthy adults: a double-blind, placebo-controlled, randomised, factorial cross-over study

Abstract: Prebiotics, probiotics and synbiotics are dietary ingredients with the potential to influence health and mucosal and systemic immune function by altering the composition of the gut microbiota. In the present study, a candidate prebiotic (xylo-oligosaccharide, XOS, 8 g/d), probiotic (Bifidobacterium animalis subsp. lactis Bi-07, 10 9 colony-forming units (CFU)/d) or synbiotic (8 g XOS þ 10 9 CFU Bi-07/d) was given to healthy adults (25 -65 years) for 21 d. The aim was to identify the effect of the supplements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 44 publications
2
97
1
2
Order By: Relevance
“…Based on a crossover trial that raised concerns over the inadequate length of a 1-mo run-in period[28], all volunteers refrained from using any commercial or trial-related probiotics over an 8-wk run-in period to reduce any putative carryover effects. A total of 83% of randomized volunteers had a history of consuming commercial probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a crossover trial that raised concerns over the inadequate length of a 1-mo run-in period[28], all volunteers refrained from using any commercial or trial-related probiotics over an 8-wk run-in period to reduce any putative carryover effects. A total of 83% of randomized volunteers had a history of consuming commercial probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the 8 RCTs of prebiotic and synbiotic supplementation are presented in Table 4 (50,51,53,66,87,88,91,92). The mean daily prebiotic dose was 10 g (range: 0.57-20 g), and the median daily probiotic dose was 5 3 10 9 CFU (range: 1 3 10 9 -8 3 10 10 CFU).…”
Section: Effects Of Prebiotics Versus Synbiotics On Systemic Inflammamentioning
confidence: 99%
“…West et al (91) observed an increase in proinflammatory IL-16 following both prebiotic and synbiotic supplementation; however, synbiotic supplementation was found to be less inflammatory, leading to an increase that was only 50% of the increase following prebiotic supplementation. Four studies, 2 of which were conducted in healthy participants, reported no significant change in inflammation in either the prebiotic or synbiotic treatment arm (50,53,88,92).…”
Section: Effects Of Prebiotics Versus Synbiotics On Systemic Inflammamentioning
confidence: 99%
“…lactis (strain Bi-07) as a synbiotic [45]. Volunteers (n = 44) were fed 8 g XOS, 109 cfu/ml bacteria, a combination of both or a maltodextrin placebo for 21 days.…”
Section: Prebiotics From Wastementioning
confidence: 99%